Impact of extended wet-aging on beef semimembranosus, gluteus medius, and biceps femoris muscles - Holloway, Maggie Elizabeth, author; Nair, Mahesh, advisor; Geornaras, Ifigenia, committee member; Chicco, Adam, committee member (Colorado State University. Libraries, 2025)
Postmortem wet aging is the most common aging method used in the meat industry to enhance tenderness, palatability, and overall consumer acceptance of beef. Previous industry surveys have indicated that the average aging time for beef is 25.9 days, while some beef cuts can be aged for up to 102 days. During postmortem aging, several microbiological and biochemical changes occur within the muscles. Most of the previous aging studies focused on the longissimus lumborum muscle. It has become more common to market single muscle cuts such as the semimembranosus (SM), gluteus medius (GM), and biceps femoris (BF). However, few studies have been conducted on microbial and biochemical changes in these muscles during aging. Therefore, the objective of this study was to determine the impact of aging on the microbial load, microbiome (16S rRNA gene sequencing and analysis), and desmin degradation of beef SM, GM, and BF. Beef top rounds (SM) and sirloin top butts (N = 80) were collected at a commercial beef processing facility. These subprimals were wet-aged for 14, 28, 35, 42, 49, 56, 63, or 70 days, and on each of these days, the BF and GM were separated from the top sirloin butt. Ten (n = 10) samples were analyzed from each muscle for each aging period. On each aging day, two separate 5 × 10 cm areas of the muscle surface were sampled using separate sponge samplers. Buffered peptone water was added to one set of sponge samples, followed by mechanical pummeling and analysis for total aerobic mesophilic microflora counts (AC) and lactic acid bacteria counts (LABC) using the TEMPO® system. To the second set of sponges, phosphate-buffered saline (PBS) was added, and after mechanical pummeling, the liquid was collected and stored at -70°C for microbiome analysis. Additionally, on each aging day, the muscles were fabricated into 2.54 cm thick steaks, frozen in liquid nitrogen, powdered, and stored at -70°C for desmin degradation analysis. After extracting bacterial DNA from the PBS meat homogenate, microbiome library preparation was performed according to the Earth Microbiome Project (https://earthmicrobiome.org/), and an Illumina MiSeq was used for sequencing. Downstream analysis was performed using the Qiime2 pipeline. Desmin degradation was analyzed using a western blotting system. The protein concentration was measured using a detergent compatible protein assay and normalized with a Coomassie blue stain. The proteins were then separated using SDS-PAGE and transferred to a PVDF membrane. Desmin was visualized using primary (polyclonal rabbit anti-desmin) and secondary (goat anti-rabbit-HRP) antibodies. All data were analyzed using R, and significance was set at α = 0.05. After downstream analysis, microbiome analysis was performed using the phyloseq, vegan, and pairwiseAdonis packages, and samples were rarefied at 4800 sequences. The relative abundance and beta diversity (Bray-Curtis and weighted UniFrac) were evaluated. The bacterial counts and desmin degradation were analyzed using the emmeans package, and the 55 kDa intact band intensity was evaluated using iBright analysis software to determine desmin degradation. All three muscles had a low microbial load (<2 log CFU/cm2) initially (day 14), which increased over time, as expected. In the SM, the AC did not increase (P > 0.05) after 28 days of aging, and LABC showed no substantial increases (P > 0.05) after 42 days. By day 70 of aging, the SM muscle had an AC of 5.6 log CFU/cm2 and LABC of 6.0 log CFU/cm2. In GM, the AC and LABC increased (P < 0.05) by 4.5 and 3.8 log CFU/cm2, respectively, from day 14 to day 42 of aging. After 42 days, no significant differences (P > 0.05) in AC and LABC were obtained in the GM muscle. The AC at 70 days of aging for the GM was 6.4 log CFU/cm2, while the LABC was 6.0 log CFU/cm2. The AC of BF did not increase (P > 0.05) after 42 days, whereas the LABC did not increase (P > 0.05) after 35 days of aging. The bacterial load of the BF muscle at 70 days of aging was 6.1 and 6.0 log CFU/cm2 for AC and LABC, respectively. For all three muscles, the Leuconostoc bacterial genus had the greatest relative abundance, followed by Carnobacterium, when averaged over all eight aging periods. Beta diversity of all the muscles decreased (P < 0.05) over time, and 14 days of aging was different (P < 0.05) from all other aging periods. Overall, there was an initial increase (P < 0.05) in desmin degradation with aging for all the muscles, but as aging time increased, there was no further increase in desmin degradation. Specifically, desmin did not degrade further after 35 days for the SM and BF and 49 days for GM. Generally, for all three muscles, the microbial load and desmin degradation increased with aging, whereas microbial diversity decreased with aging. Aside from the initial 14-day aging period, the most abundant bacterial genera were lactic acid bacteria. A higher degree of desmin degradation was observed with an increase in aging times for all the muscles, which could lead to increased tenderness. While there were some differences in microbial load, microbial diversity, and desmin degradation during early aging days, those disappeared as the aging time increased. Overall, these results suggest that a longer aging period for these muscles does not necessarily yield a higher-quality product.